Maternal levels of endocrine disrupting chemicals in the first trimester of pregnancy are associated with infant cord blood DNA methylation - Montrose, Luke (Epigenetics, 2018)
Endocrine disrupting chemicals (EDCs) pose a public health risk through disruption of normal biological processes. Identifying toxicoepigenetic mechanisms of developmental exposure-induced effects for EDCs, such as phthalates or bisphenol A (BPA), is essential. Here, we investigate whether maternal exposure to EDCs is predictive of infant DNA methylation at candidate gene regions. In the Michigan Mother-Infant Pairs (MMIP) cohort, DNA was extracted from cord blood leukocytes for methylation analysis by pyrosequencing (n = 116) and methylation changes related to first trimester levels of 9 phthalate metabolites and BPA. Growth and metabolism-related genes selected for methylation analysis included imprinted (IGF2, H19) and non-imprinted (PPARA, ESR1) genes along with LINE-1 repetitive elements. Findings revealed decreases in methylation of LINE-1, IGF2, and PPARA with increasing phthalate concentrations. For example, a log unit increase in ΣDEHP corresponded to a 1.03 [95% confidence interval (CI): −1.83, −0.22] percentage point decrease in PPARA methylation. Changes in DNA methylation were also inversely correlated with PPARA gene expression determined by RT-qPCR (r = −0.34, P = 0.02), thereby providing evidence in support of functional relevance. A sex-stratified analysis of EDCs and DNA methylation showed that some relationships were female-specific. For example, urinary BPA exposure was associated with a 1.35 (95%CI: −2.69, −0.01) percentage point decrease in IGF2 methylation and a 1.22 (95%CI: −2.27, −0.16) percentage point decrease in PPARA methylation in females only. These findings add to a body of evidence suggesting epigenetically labile regions may provide a conduit linking early exposures with disease risk later in life and that toxicoepigenetic susceptibility may be sex specific.